KARAKTERISTIK TOKOH BUNGKUN DALAM CERITA RAKYAT DAYAK NGAJU, KALIMANTAN TENGAH - Yudianti Herawati (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2017)
This paper aimed to reveal and describe the intrinsic and extrinsic structures depicted in Bungkun story of Dayak Ngaju people, Central Kalimantan. The problem that arose in this research was limited to the analysis of Bungkun’s character. It used structuralism and oral literature theories to analyze the cultural values, belief, ingenuity, and characters’ exemplification in the story of Bungkun. This research used qualitative method and descriptive analytical techniques. It discussed the story of Dayak Ngaju folklore that brought many values of good characters, exemplification, and advices that shaped the characters of the local community better and made their personal and social life qualified. It showed that Bungkun was an ordinary human who had a unique character in living his life and ingenuity in dealing with his poverty so that Bungkun became a role model for Ngaju people.